Part II : policy instruments for sustainable road transport - Santos, G; Behrendt, H; Teytelboym, A (Elsevier, 2010)
Without questioning the fact that to achieve efficiency emitters should pay for the true costs of their actions (a core principle of economic policies such as pollution taxes), we find sufficient evidence in the literature to demonstrate that many other policy instruments can be used in combination with taxes and permits to ensure that the transport needs of the present generation can be met without compromising the ability of future generations to meet any needs of their own., , The policies and policy aspects considered in this paper broadly fall into three categories: physical policies, soft policies and knowledge policies. All three aim to bring about changes in consumers’ and firms’ behaviour, but in different ways. The first category includes policies with a physical infrastructure element: public transport, land use, walking and cycling, road construction and freight transport. We also consider the particular challenges for mobility in developing countries and how these may be addressed. Soft policies, on the other hand, are non-tangible aiming to bring about behavioural change by informing actors about the consequences of their transport choices and potentially persuading them to change their behaviour. These measures include car sharing and car pooling, teleworking and teleshopping, eco-driving, as well as general information and advertising campaigns. Finally, knowledge policies emphasise the important role of investment in research and development for a sustainable model of mobility for the future.